Platelet Function Assays for the Diagnosis of Aspirin Resistance. (3rd April 2022) - Van Oosterom, Nameer; Barras, Michael; Cottrell, Neil; Bird, Robert
Abstract: Aspirin, an antiplatelet drug, is commonly used at low doses for numerous indications, including prophylaxis of cardiovascular, neurovascular, and venous thromboembolic events. Due to review articles suggesting that aspirin resistance may result in poorer outcomes, interest in assessing platelet function is increasing. Despite this, platelet function tests are rarely used as part of routine clinical practice and therefore, a basic understanding of these tests may be lacking. Although aspirin resistance can be categorized as clinical or laboratory resistance, determining laboratory resistance is the only way to determine resistance before treatment failure occurs. Therefore, knowledge of platelet assays to determine aspirin resistance is of importance. The following review aims to provide a framework for clinicians to understand the main principles of platelet function tests. This includes comparison of the most frequently used platelet assays to diagnose aspirin resistance, including the basic mechanism, methodology, reference ranges, inter-assay comparison, and their respective clinical considerations when using.